Endocrine control of oogenesis in teleosts - Fard, Ehsan Ramezani; Kamarudin, Mohd Salleh; Harmin, Sharr Azni (Academic Journals, 2013)
Production of large amounts of fish eggs with high quality is one of the major goals in aquaculture industry. All reproductive processes in fish are regulated by endocrine system. Numerous studies have been carried out in recent years in order to develop or improve egg production protocols. This study provides a summary of some recent advances regarding fish oocyte differentiation, maturation and ovulation stages. The oocyte growth stages including first and second growth stages, veitellogenesis and final growth stage and maturation are briefly explained. Recent advances on the hormonal systems which control the reproductive process and oocyte development are also highlighted.